Occasional Tillage and Nitrogen Application Effects on Winter Wheat and Grain Sorghum Yield - Augustine K. Obour; John D. Holman; Alan J. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2020)
Occasional tillage ahead of winter wheat planting could alleviate herbicide-resistant weeds, redistribute soil acidification, and improve seedbed at wheat planting. The objective of this study was to determine occasional tillage and nitrogen (N) fertilizer application effects on winter wheat, and grain sorghum yields and soil quality in a wheat-sorghum-fallow cropping system. Treatments were three tillage practices: 1) continuous no-tillage (NT); 2) continuous reduced-tillage (RT); and 3) single tillage operation every 3 years (June-July) ahead of winter wheat planting [occasional tillage (OT)]. The sub-plot treatments were assigned to four N fertilizer rates (0, 40, 80, and 120 lb/a of N). Results showed tillage had no effect on winter wheat grain yield. Averaged across the 2 study years, wheat yields were 29.4 bu/a with NT, 31.0 bu/a with RT, or 31.6 bu/a with OT. Applying N fertilizer increased wheat yield, ranging from 20 bu/a with no N fertilizer to 38.7 bu/a when N fertilizer was applied at 120 lb/a of N. However, tillage (P= 0.04) and year × N rate interaction (P= 0.003) had significant effect on grain sorghum yield. Average grain sorghum yield with RT (73.6 bu/a) was less than NT (79.4) or OT (75.4 bu/a). Averaged across tillage and years, sorghum grain yield was 60.3 bu/a with no N fertilizer and 86.8 bu/a when N was applied at 120 lb/a of N. In most years, sorghum and winter wheat grain yields obtained with 80 lb/a of N were not different from those with 120 lb/a of N, suggesting 80 lb/a of N may be adequate for both crops.
Keywords: nitrogen; occasional tillage; sorghum; winter wheat